Pengaruh Penerapan Model Pembelajaran RADEC (Read, Answer, Discuss, Explain, Create) terhadap Kemampuan Berpikir Kritis Matematis Peserta Didik - Yuliany, Nur; Latuconsina, Nur Khalisah; Nursalam; Abrar, Andi Ika Prasasti; Wahyuni, Ira (Al Asma: Journal of Islamic Education, 2023)
This research aims to get an overview of (1) the mathematical critical thinking abilities of students who do not apply the RADEC learning model, (2) the mathematical critical thinking abilities of students who apply the RADEC learning model, (3) the influence of the RADEC learning model on participants' mathematical critical thinking abilities educate. This research approach is a quantitative approach with a type of experimental research. The population in this study was all students in class VIII of SMP Negeri 24 Bulukumba. The sample was all students in class VIII B and class VIII C, with 22 students each taken using the Simple Random Sampling technique. The instrument used in this research is a test instrument in the form of essay questions. The analysis technique used is descriptive and inferential statistical analysis with hypothesis testing using the independent sample t-test. (1) The control class pretest results have a percentage of 100% in the very low category, and the control class posttest results have a percentage of 4.5% in the very low category. (2) The experimental class pretest results had a percentage of 100% in the very low category, and the experimental class posttest results obtained were 13.6% in the medium category. (3) The results of the inferential analysis showed that the RADEC (Read, Answer, Discuss, Explain, Create) learning model affected the mathematical critical thinking abilities of Class VIII students at SMP Negeri 24 Bulukumba.